Analisis Pengendalian Persediaan Barang Dagangan Serta Audit Internal “Coso Framework” Dalam Menilai Efektivitas Dan Efisiensi Pengendalian Persediaan Barang Dagangan PT. Mitra Fajar Selaras Surabaya - Susanto Susanto; Tri Ratnawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
PT Mitra Fajar Selaras Surabaya is a company engaged in the trading of medical equipment, particularly in the field of bone and nerve surgery. Inventory of goods is a valuable asset for a trading company. Internal control of merchandise inventory is crucial for supervision and security purposes to prevent fraudulent activities that can result in company losses. This research aims to analyze whether the internal control of merchandise inventory at PT Mitra Fajar Selaras Surabaya is effective and efficient according to the COSO ERM Integrated Framework. This research is a qualitative descriptive study, and the data collection methods used include observation, questionnaires, literature review, and documentation. The results of this research show that the internal control of merchandise inventory implemented by PT Mitra Fajar Selaras Surabaya is quite effective and efficient. However, there are still findings regarding several aspects that do not fully comply with the components of the COSO ERM Integrated Framework.